An Analysis of Purchasing and Consumption Preferences for Foie Gras and Foie Gras-based Products - Fazekas, Ádám; Vincze, Judit; Herczeg, Béla; Szabóné Béres, Beatrix (Journal of Central European Green Innovation, 2022)
In Hungary, the production of fattened geese is not only of gastronomic and cultural importance, but also plays a very important role in the national economy. Hungary is among the absolute leaders in goose production in Europe. Products made from fattened geese are considered a real speciality in the world, and in Hungary fattened goose liver is a Hungaricum product. There is a basic seasonality in the demand for goose products, especially for liver and meat, and the end-users of fattened liver products are mainly catering service providers due to its high price (Internet 1). In the light of recent epidemics (COVID_19, poultry flu), tightening animal welfare rules and campaigns by animal welfare organisations, the future of the sector is uncertain, and it is important to know domestic habits in order to develop a realistic vision of the sector.In the course of our work, a questionnaire survey was carried out on the purchasing and consumption preferences of foie gras-based products. Our research objectives were to identify the purchasing and consumption habits of the Hungarian population in relation to foie gras and foie gras-based products, including a comparative analysis, to identify the factors and parameters that encourage the purchase and consumption of the products and to assess the frequency of consumption of foie gras. The extent to which consumers consider the product to be a gastronomic curiosity and the absolute characteristic of domestic consumption is that people associate the consumption of foie gras with a particular occasion. Our survey also asked which of the Hungarian or foreign foie gras products the respondents preferred.
Keywords: questionnaire survey; customer preferences; consumer preferences; foie gras; foie gras-based products